An analytical study of some of the deterministic variables of the stage of advancement and its relation to the accuracy of the performance of the skill of high jump correction - م.م. سكنة عبد الرزاق طارش أ.دبشرى كاظم أ.د. انتصار كاظم (physical education and sport sciences college for women/ Baghdad University, 2018)
Introduction, importance and problem of researchthe researcher dealt with the game of handball in general and the skill of jumping high, "in particular, which is an important offensive skills in the handball game and the most important types of correction and most used," This is what most of the specialists and the operators of the training because it is more influential " Accuracy in performance. The importance of research in the analysis of some of the kinetic variables for the advancement of the skill of high jump correction "and their relationship to motor accuracy. The problem of research is the weakness in the kinetic variables of the stages of skill performance of the skill of skipping high jump, "which leads to a poor accuracy of the correction towards the goal. Therefore, the aim of the research was to identify some of the kinetic variables for the advancement stage of the skill of high jump correction "and its relation to the motor accuracy of the players of the national team. The researcher used the descriptive approach to suit the nature of the research. The sample was from the players of the national handball team and applied the accuracy of the correction and video filming in the hall of the training center for sports talent of handball at the Ministry of Youth and Sports using modern cameras and SPSS program for statistical data extraction. The data obtained by the researcher from the analysis of kinetic variables were discussed with each other and their relation to motor accuracy was a scientific discussion and obtained several significant conclusions, including significant correlation between kinematic variables for the stage of advancement, maximum flexion of the knee joint at the moment of focus and the angle of the knee joint at the moment of advancement. A significant correlation was also shown between kinematic variables between the angle of the hip joint and the elevation angle. Theresearcher also made several recommendations, including that it is necessary to be angles in the hip joint and knee as low as possible and height of the hip stage of advancement, which gets low angle of approach to get speed at the moment of advancement. As well as interest in the advancement phase through the use of deep jump exercises